Original researchTreatment with double dose of omeprazole increases -endorphin plasma level in patients with coronary artery disease - Budzyński, Jacek; Pulkowski, Grzegorz; Kłopocka, Maria; Augustyńska, Beata; Sinkiewicz, Anna; Suppan, Karol; Fabisiak, Jacek; Majer, Marcin; Świątkowski, Maciej (Archives of Medical Science, 2010)
Introduction: The proton pump inhibitor empirical trial, besides the analysis of symptoms, is the main method in the diagnosis of gastro-oesophageal reflux disease-related chest pain. β-Endorphin acts as an endogenous analgesia system. The aim of the study was verify whether β-endorphin plasma level is affected by omeprazole administration and influences the severity of anginal symptoms and outcome of the “omeprazole test” in patients with coronary artery disease (CAD) and chest pain of suspected non-cardiac origin. Material and methods: Omeprazole was administered to 48 patients with CAD in a randomized, placebo -controlled, crossover study design. At the beginning of the study, and again after the 14-day omeprazole and placebo treatment, the β-endorphin plasma concentration was determined. Results: The level of plasma β-endorphin after the administration of omeprazole was significantly greater than at the start of the study and following the placebo . Responders to omeprazole had an average lower β-endorphin plasma concentration than subjects who failed to respond to this therapy. Subjects with symptoms in class III (according to the Canadian Cardiovascular Society classification) after omeprazole administration had a greater β-endorphin plasma level than subjects in class II for anginal symptom severity. Conclusions: Fourteen-day therapy with a double omeprazole dose significantly increases the β-endorphin plasma concentration in patients with CAD. Circulating β-endorphin does not seem to be involved in the mechanism for the “omeprazole test” outcome, although an individually different effect on pain threshold cannot be excluded.